Integrative Islamic Religious Education as a Transformational Pathway to Sustainable Character and the Sustainable Development Goals (SDGs) - Muhammad Eko Arief Wijaksono; Moh. Affan; Siswanto; Mona Novita (Educazione: Journal of Education and Learning, 2026)
The Sustainable Development Goals have placed education at the center of global efforts to build a more equitable and sustainable world, yet much of the discourse still treats sustainability as a cognitive and policy matter, leaving its moral and spiritual foundations underdeveloped. Within this gap, Islamic Religious Education holds considerable but insufficiently theorized potential, since existing studies tend to affirm the correspondence between Islamic values and sustainability without explaining how it becomes educationally consequential. This study aims to reconstruct how Integrative Islamic Religious Education can serve as a strategic framework for embedding sustainability values within character education. Employing a qualitative library research design through a systematic library review, it analyzes peer-reviewed scholarship published between 2015 and 2025 using thematic content analysis. The findings show that integration operates not by adding new content but through value internalization, curriculum contextualization, and experiential learning, in which principles such as ‘adl (justice), amanah (responsibility), rahmah (compassion), and khalifah fil ardh (stewardship of the earth) are aligned with sustainability as shared moral commitments rather than imposed secular targets. The analysis locates integration at the axiological rather than the epistemological level and identifies pedagogy as the decisive mechanism that translates values into sustainable character. The principal implication concerns transformational education and learning, since the study frames Islamic ethical values as interpretive frames through which learners are reoriented toward sustainability at the level of disposition and worldview, offering a religiously grounded model of transformational pedagogy that now awaits empirical testing.